Intimate partner violence and pregnancy: a systematic review of interventions. - An-Sofie Van Parys; Annelien Verhamme; Marleen Temmerman; Hans Verstraelen (PLoS ONE)
Background Intimate partner violence (IPV) around the time of pregnancy is a widespread global health problem with many negative consequences. Nevertheless, a lot remains unclear about which interventions are effective and might be adopted in the perinatal care context. Objective The objective is to provide a clear overview of the existing evidence on effectiveness of interventions for IPV around the time of pregnancy. Methods Following databases PubMed, Web of Science, CINAHL and the Cochrane Library were systematically searched and expanded by hand search. The search was limited to English peer-reviewed randomized controlled trials published from 2000 to 2013. This review includes all types of interventions aiming to reduce IPV around the time of pregnancy as a primary outcome, and as secondary outcomes to enhance physical and/or mental health, quality of life, safety behavior, help seeking behavior, and/or social support. Results We found few randomized controlled trials evaluating interventions for IPV around the time of pregnancy. Moreover, the nine studies identified did not produce strong evidence that certain interventions are effective. Nonetheless, home visitation programs and some multifaceted counseling interventions did produce promising results. Five studies reported a statistically significant decrease in physical, sexual and/or psychological partner violence (odds ratios from 0.47 to 0.92). Limited evidence was found for improved mental health, less postnatal depression, improved quality of life, fewer subsequent miscarriages, and less low birth weight/prematurity. None of the studies reported any evidence of a negative or harmful effect of the interventions. Conclusions and implications Strong evidence of effective interventions for IPV during the perinatal period is lacking, but some interventions show promising results. Additional large-scale, high-quality research is essential to provide further evidence about the effect of certain interventions and clarify which interventions should be adopted in the perinatal care context.